Ruthenium Carboxylate Complexes as Efficient Catalysts for the Addition of Carboxylic Acids to Propargylic Alcohols (Eur. J. Inorg. Chem. 18/2015). Issue 18 (June 2015) - Jeschke, Janine; Gäbler, Christian; Korb, Marcus; Rüffer, Tobias; Lang, Heinrich
Abstract : The cover picture shows the atom‐economical and highly selective addition of carboxylic acids to propargylic alcohols to give β‐oxopropyl esters. As background picture, one of the most famous sights of Chemnitz, the hometown of the authors, was chosen. It shows the bust of Karl Marx, in whose honor the city was named Karl‐Marx‐Stadt from 1953 to 1990. Today, this monument is not only a must‐see for tourists but also the local meeting point for young skateboarders. One of these skateboarders represents the catalyst in our conversion. After coordinating the substrates, the ruthenium catalyst enhances the reaction by speeding it up and leading the substrates through the catalytic cycle, which is demonstrated by the dark‐yellow loop. The pictures of the skaters are adopted from Fotolia (Copyright aroas/fotolia.com). We acknowledge graphic designer Jacob Müller from University Communications TU Chemnitz for graphic implementation of our concept into this picture. Details are discussed in the article by H. Lang et al. onp. 2939 ff . For more on the story behind the cover research, see theCover Profile .